The Handbook on optical constants of metals : in tables and figures - Adachi, Sadao, 1950- (World Scientific Pub., 2012)
This book presents data on the optical constants of metal elements (Na, Au, Mg, Hg, Sc, Al, Ti, ß-Sn, V, Cr, Mn, Fe, La, Th, etc.) semimetal elements (graphite, Sb, etc.), metallic compounds (TiN, VC, TiSi 2 , CoSi 2 , etc.) and high-temperature superconducting materials (YBa 2 Cu 3 O 7-d , MgB 2 , etc.). A complete set of the optical constants are presented in tabular and graphical forms over the entire photon-energy range. They are: the complex dielectric constant e( E )=e 1 ( E )+ie 2 ( E ), the complex refractive index n *( E )= n ( E )+i k ( E ), the absorption coefficient a( E ) and the.
Keywords: Metal coating.; Metallizing.; Polymers -- Surfaces.; elektronické knihy; electronic books